Using Instructional Monitoring to Improve the Learning Process - Herliana, Herliana (PPSDP International Journal of Education, 2022)
Educational supervision is one method of offering professional help to teachers in order to improve their abilities to manage the learning process efficiently and effectively. The goal of this research was to determine how the learning process was carried out by the instructor after being monitored. The madrasa principal, as a supervisor, must conduct out supervision operations in schools, as well as different supervisory and control activities to enhance teacher performance in learning process activities. Supervision and control are preventive methods to keep instructors from deviating from their duties as educators and to make them more cautious. As a result, this study exposes the supervisory activities carried out on instructors by the Head of Madrasah MTs Negeri 1 Prabumulih City. A descriptive-qualitative technique is used in this investigation. The principal and instructors were the topics of this investigation. This research discusses a variety of topics related to the difficulties addressed. Following that, data was gathered through observation, interviews, and documentation. According to the findings of this study, the presence of supervision activities can help teachers solve educational problems that frequently arise when carrying out teaching and learning activities, as well as motivate teachers to always increase their knowledge in order to become professional teachers in carrying out the learning process.